Simvastatin Preferentially Targets FLT3/ITD Acute Myeloid Leukemia by Inhibiting MEK/ERK and p38-MAPK Signaling Pathways - Genhong Li; Jingwei Yao; Zhen Lu; Lian Yu; Qinwei Chen; Lihong Ding; Zhihong Fang; Yin Li; Bing Xu (Adis, Springer Healthcare, 2023)
Abstract Background The FLT3/ITD mutation exists in many acute myeloid leukemia (AML) patients and is related to the poor prognosis of patients. In this study, we attempted to evaluate the antitumor activity of simvastatin, a member of the statin class of drugs, in vitro and in vivo models of FLT3/ITD AML and to identify the potential mechanisms. Methods Cell Counting Kit-8 (CCK-8) and Annexin V/propidium iodide (PI) staining kits were used to detect cell viability and apoptosis, respectively. Subsequently, Western blot and rescue experiment were applied to explore the potential molecular mechanism. In vivo anti-leukemia activity of simvastatin was evaluated in xenograft mouse models. Results In vitro experiments revealed that simvastatin inhibited AML progression in a dose- and time-dependent manner, while in vivo experiments showed that simvastatin significantly reduced tumor burden in FLT3/ITD xenograft mouse models. After simvastatin treatment of FLT3/ITD AML cells, intracellular Rap1 was downregulated and the phosphorylation levels of its downstream targets MEK, ERK and p38 were significantly inhibited. The rescue experiment showed that mevalonate, an intermediate product of the metabolic pathway of mevalonate, and its downstream geranylgeranyl pyrophosphate (GGPP) played a key role in this process. Finally, we demonstrate that simvastatin can induce apoptosis of primary AML cells, while having no effect on peripheral blood mononuclear cells from normal donors. Conclusions Simvastatin can selectively and effectively eradicate FLT3/ITD AML cells in vitro and in vivo, and its mechanism may be related to the disruption of the HMG-CoA reductase pathway and the downregulation of the MEK/ERK and p38-MAPK signaling pathways.